Introductory editorial thematic issue: advances in geochemistry of the surface in Argentina - Torres, Américo Iadran (2018)
Geochemistry involves the study of the distribution, proportion, and association of chemical elements of the earth’s crust that are present in different matrices such as water (sweet, saline, residual, rain, underground), soils, minerals, sediments, rocks, and air. Initially, this discipline was only used to study the composition and formation of rocks, but nowadays simultaneously relates geology to chemistry.